Image Bandung Culinary Travel Destination As Seen From The Perception of Tourists to The City of Bandung - Deden Firman Syuyaman Rukma (Jurnal Wacana Ekonomi, 2018)
With the increase in tourists visiting the city of Bandung either locally or foreigner provide a very positive impact for the development of the tourism industry. Researchers highlight the culinary tourism because tourism product still very rare to be studied, which in fact provide tremendous value to the image formation. The purpose of the study was to describe the perception of tourist to the city’s image from the aspects of cognitive Bandung culinary, travellers describe the perception of the image of the city of London seen from the affective aspects of culinary tourism in Bandung, also explains the perception of tourists to the overall image of the city of Bandung as a culinary tourism. Results are expected to assist stakeholders in developing the availability of facilities at the site of a culinary tour of Bandung city, so travellers can further increase the desire to revisit the city of Bandung. Bandung city government should continue to improve and develop the potential of the attractiveness, uniqueness, and diversity of the typical culinary offerings in the city in a structured and focused, which in turn can make the city of Bandung as a superior culinary tourism destination.